Identification of Ethical and Medicolegal Problems in the Care of Patients in the Intensive Care Unit - Taufik Suryadi; Kulsum (Britain International for Academic Research (BIAR) Publisher, 2020)
Intensive care is an important part of a hospital that serves patients with critical illness conditions and requires continuous medical supervision and support. The complexity of the problems related to intensive care results in ethical and medicolegal problems. Some of the ethical and medicolegal problems identified can be in the form of priority problems for patients entering and leaving the intensive care room, facility limitations, treatment is useless, terminal state, directive advances, do not resuscitate, brain stem death, euthanasia, and micro-ethical problems that arise directly during patient care which can cause a bad experience for patients and reduce the quality of service. Problem solving can be done by applying clinical ethics, basic principles of bioethics and medicolegal as well as effective communication. Doctors who work in intensive care installations must have the ability to determine patient priorities, be able to communicate well with patients and / or their families, and be able to provide end-of-life care based on basic principles of bioethics. This capability will lead to good and complete medical services.